43. NUTRITIONAL STATUS AND SERUM ZINC CONCENTRATION WITH CHILDREN AGED 0-36 MONTHS VISITED FOR NUTRITION COUNSELLING THE DR. NUTRI NUTRITION CLINICS, 2023-2024 (Tạp chí Y học Cộng đồng, 2024)
Objective: To evaluate the nutritional status and serum zinc concentration and some related factors of children 0-36 months.Methods: Cross-sectional description based on medical records of 245 children.Results: The rate of malnutrition wasting was 5.3%, stunting was 17.5% and underweight was 8.6%, notably the rate of overweight and obesity was 9.4% and there was a statistically significant difference between the 2 age groups with p
Keywords: Nutritional status; serum zinc; children